2021
DOI: 10.1108/arj-08-2020-0240
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting on accounting academics’ motivation and capacity to adapt in challenging times

Abstract: Purpose The purpose of this paper is to consider what factors influence the ability of academic staff to remain motivated and to persist in their work environment during the COVID-19 pandemic. Tinto’s (2017) model of student motivation and persistence is reconceptualised to apply to the academic staff by considering their self-efficacy beliefs, sense of belonging and perceptions of career relevance on their motivation levels and adaption to a new environment. Design/methodology/approach Utilising Tinto’s (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 36 publications
0
24
0
6
Order By: Relevance
“…466-469). The second is a methodological contribution by using a qualitative survey of national scope (de Villiers et al, 2019(de Villiers et al, , p. 1470; most of the previous works were autoethnographic (Ackermann, 2021;Alam, 2020;Beatson et al, 2021;G omez and Alba, 2021;Haynes, 2020;Othman, 2021;Powell and McGuigan, 2020;Wong and Zhang, 2020). Finally, the complete model of Paulo Freire used before in accounting education is taken up Bebbington, 2004, 2005), beyond some ideas recently taken from Pedagogy of Freedom and Pedagogy of Hope to analyse the effects of the pandemic (Powell and McGuigan, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…466-469). The second is a methodological contribution by using a qualitative survey of national scope (de Villiers et al, 2019(de Villiers et al, , p. 1470; most of the previous works were autoethnographic (Ackermann, 2021;Alam, 2020;Beatson et al, 2021;G omez and Alba, 2021;Haynes, 2020;Othman, 2021;Powell and McGuigan, 2020;Wong and Zhang, 2020). Finally, the complete model of Paulo Freire used before in accounting education is taken up Bebbington, 2004, 2005), beyond some ideas recently taken from Pedagogy of Freedom and Pedagogy of Hope to analyse the effects of the pandemic (Powell and McGuigan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The emerging literature on accounting education in the COVID-19 context has focussed on faculty autoethnography and undergraduate students studies. The group of articles on faculty describes recent teaching experiences (Ackerman, 2021;Beatson et al, 2021;G omez and Alba, 2021;Haynes, 2020;Mai, 2020;Powell and McGuigan, 2020;Stewart and Khan, 2021;Wong and Zhang, 2020) whilst the other group highlights student responses and challenges (Ali et al, 2020;Bowyer, 2021;Dyki et al, 2021;Malan, 2020;Pasion et al, 2021;Reyneke et al, 2020). There is also a paper on graduate students (Ramachandra and Wells, 2021) and another one on the training of instructors for online education (Sadiq, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not have to be at the expense of flexibility, but it does mean that we have to think differently about the sharing of responsibilities between academics, accountants and students. COVID-19 has also had very different impacts on the two professions of accounting and academia (Beatson et al , 2021). Universities, including their academics, appear to be most vulnerable to the pandemic, making economic and social sacrifices to protect learners.…”
Section: Discussionmentioning
confidence: 99%
“…This combination of academic freedom and emphasis on professional judgement enables academics to demand that learners work hard and actively engage with stimulating and at times, uncomfortable ideas and move forward (Ackermann, 2021). Beatson et al (2021) have found that academics build resilience through facing major challenges and obstacles. This provides a renewed vision into how academic traditions, such as collegiality, commitment to teaching and research excellence, may help academics to adapt to new challenges, perhaps better than their counterparts in a traditional corporate environment.…”
Section: Discussionmentioning
confidence: 99%